Strengthening Educational Quality in Islamic Schools: The Strategic Role of Public Relations and Public Services - Moh. Rifa'i; Viviana Dewi Safitri; Mohammad Bahrul Ulum (Journal of Educational Management Research, 2026)
This study aims to analyze the contribution of public relations management and public services to strengthening the quality of madrasah education. The study was motivated by the growing importance of public relations and service quality in building public trust, community participation, and a positive institutional image within increasingly complex educational demands. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The study was grounded in Grunig and Hunt’s Two-Way Symmetrical Theory and Stakeholder Theory. The findings reveal that public relations management and public services functioned in an integrated and participatory manner, despite the absence of a formal public relations structure. Dialogic communication, student-oriented services, collaborative relationships with parents, and well-planned resource management contributed significantly to improving educational quality. The implications of this study emphasize that public relations play a strategic role in strengthening institutional quality, stakeholder satisfaction, and the sustainability of educational programs in madrasah education.